TRAUMATISM IN TRAINING PROCESS OF STUDENTS - VOLLEYBALL PLAYERS - V.Ya. Kovalchuk (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to analyze traumas in training process of students-volleyball players. Material: 42 students participated in the research. Students' medical records were analyzed in the research. Results: with every year of study in university the quantity of traumas decreased. In 1st year students we found 10 traumas, in 4th year - 5. Ligament sprains are the most frequent kinds of traumas. In total we found 33.3%. Their main part covers ankle joint traumas. The reasons of them are bursts, stops, changes of movements' direction. Rather frequents (30%) are maims of knee and elbow joints, caused by falling down. The degree of joints' injury is, as usually, negligible. The highest quantity of moderate and heavy traumas was among 1st year students (9 from 10) and 2nd year students (8 from 8). Conclusions: prophylaxis complex for prevention of volleyball traumas has been offered. Volleyball traumas' prevention implies improvement methodic and technique of students-volleyball players' training. The main reasons of traumatism are the following: non observation of sports training principles; poor organizational and logistical support of training process.